The Role of Authentic Leadership in Improving Healthcare Workers Performance and Hospital Service Quality - Dian Mawarni (International Journal of Economics and Management Sciences, 2026)
Hospitals play a strategic role in improving public health through professional, safe, and high-quality healthcare services. In modern healthcare organizations, service quality is not only determined by medical facilities and technology but also by the quality of human resources, particularly healthcare workers who directly interact with patients. This study aims to analyze the influence of authentic leadership on healthcare workers’ performance and hospital service quality. The study employed a quantitative explanatory research design involving 120 healthcare workers in a hospital setting. Data were collected using questionnaires and analyzed through multiple linear regression analysis. The findings demonstrate that authentic leadership has a positive and significant effect on healthcare workers’ performance, with a regression coefficient value of 0.648 and a significance level of 0.000. Furthermore, authentic leadership indirectly influences hospital service quality through healthcare workers’ performance, with an indirect effect value of 0.521. These findings indicate that leaders who demonstrate honesty, transparency, integrity, and interpersonal support are able to create a healthy work environment that enhances healthcare workers’ motivation, responsibility, and professionalism. Consequently, improved employee performance contributes to better hospital service quality, particularly in responsiveness, empathy, and communication with patients. This study highlights that authentic leadership is an effective leadership approach for strengthening healthcare human resources and improving hospital service quality in contemporary healthcare organizations.